2023
DOI: 10.1609/aaai.v37i4.25514
|View full text |Cite
|
Sign up to set email alerts
|

Solving Explainability Queries with Quantification: The Case of Feature Relevancy

Abstract: Trustable explanations of machine learning (ML) models are vital in high-risk uses of artificial intelligence (AI). Apart from the computation of trustable explanations, a number of explainability queries have been identified and studied in recent work. Some of these queries involve solving quantification problems, either in propositional or in more expressive logics. This paper investigates one of these quantification problems, namely the feature relevancy problem (FRP), i.e.\ to decide whether a (possibly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Finally, although Shapley values are a convenient mathematical technique for understanding model behavior to some extent, it is crucial to acknowledge that there are limitations to this technique, including prior studies that have suggested that results can sometimes be inaccurate and misleading. 21 , 22 Therefore, it is still essential to consider explainability results in the context of prior similar studies and overall established medical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although Shapley values are a convenient mathematical technique for understanding model behavior to some extent, it is crucial to acknowledge that there are limitations to this technique, including prior studies that have suggested that results can sometimes be inaccurate and misleading. 21 , 22 Therefore, it is still essential to consider explainability results in the context of prior similar studies and overall established medical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Explanability queries -feature relevancy [32], [34], [35]. Let us consider a classifier M, with features F , domains D i , i ∈ F , classes K, a classification function κ : F → K, and a concrete instance (v, c), v ∈ F, c ∈ K.…”
Section: Cxp(y)mentioning
confidence: 99%